Risk Mitigation Of Rice Production In Pringsewu District - Aldilla, Siti Hafsyoh; Haryono, Dwi; Rosanti, Novi (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
This research aims to identify sources of risk that cause production risks in rice commodities, analyze the impact and probability of production risks occurring, and analyze production risk management for handling production risks that rice farmers must carry out in Pringsewu Regency. This research was conducted on lowland rice farmers in Pringsewu Regency. The sampling technique used was purposive sampling with a total sample of 67 people. The analytical tool used to answer the aim of identifying risk sources uses qualitative descriptive analysis. The probability and impact of production risks are analyzed using the Z-score and Value at Risk methods. Meanwhile, risk management is analyzed using a risk management matrix. Analysis results using z-score indicate a risk probability of 3%. The results of the analysis using the Value at Risk method shows a risk impact of IDR 2,726,743 -. Risk management carried out by farmers based on the risk management matrix is insurance. Other mitigation measures that farmers can carry out include creating irrigation channels, pumping programs and using pesticides.